Optimalisasi Peran Santri Pondok Pesantren Di Era Digital Dalam Mewujudkan Kemampuan Berwirausaha - Mas Ghoniyyul Hamid (Journal of Islamic Economic and Business Studies, 2023)
The purpose of this research is to elaborate on efforts to optimize Islamic boarding school students in realizing technology-based entrepreneurial abilities. Islamic boarding school students have very low digital economic capabilities, which causes a negative stigma against students who are considered old-fashioned to this day. This research method uses descriptive qualitative research using primary data sources and secondary data sources as a means of obtaining data and using descriptive analysis in data analysis techniques. The results of this study are (1) the role of santri is very strong in supporting the progress of entrepreneurship and technology at this time (2) various Islamic boarding schools can develop the BMT UGT Sidogiri and Basmalah Supermarket cooperatives as a manifestation of the progress of Islamic boarding schools and students in the field of entrepreneurship